The Professionalism of Educators in Kindergarten Education Management: A Literature Review - Dewi, Sri Nursam; Mokodompit, Eliyanti Agus; Zubair, Yuyun Nirwana (International Publisher (YAPENBI), 2025)
The professionalism of educators in the management of kindergarten education is a fundamental factor in guaranteeing the quality of early childhood education services. This study aims to analyze the concepts, dimensions, and challenges of kindergarten teacher professionalism through a literature review of relevant national and international journals, books, and research reports. The findings of the review indicate that the professionalism of kindergarten teachers is proven to be highly determinant of the quality of early childhood learning and is influenced by pedagogical competence, academic supervision, and school principal management. Suboptimal supervision and weak evaluation of training are the main obstacles to improving teacher performance. Competence development is proven to have a positive impact, but it is not yet evenly distributed due to limitations in facilities, experience, and access to learning. Furthermore, internal and external factors such as motivation, administrative burden, and working conditions significantly affect the teachers' sustained professionalism.